The Contribution of Institutional Resilience to Crisis Management in Government Schools in the Sultanate of Oman (The International Journal for Scientific Research, 2026)
This study aimed to examine the level of institutional resilience and crisis management in public schools in the Sultanate of Oman, and to analyze differences in teachers’ perceptions according to the variables of school type (gender-based), and educational stage. It also sought to investigate the correlational relationship between institutional resilience and crisis management, as well as to determine the extent to which the dimensions of institutional resilience contribute to predicting crisis management. To achieve these objectives, a descriptive correlational approach was employed, and a validated questionnaire was administered to a sample of (1,050) teachers from various educational governorates.The results indicated that the level of institutional resilience was high, with a mean score of (3.92), and that the level of crisis management was high. The findings further revealed statistically significant differences in teachers’ perceptions attributable to the variables of school type, and educational stage. Moreover, a strong positive and statistically significant correlation was found between institutional resilience and crisis management. The results of multiple linear regression analysis confirmed that institutional resilience significantly explains the variance in crisis management, accounting for (88%), with the dimensions of responsiveness and adaptability exerting the greatest influence compared to continuous learning.The study recommends enhancing institutional resilience practices in schools through the development of specialized training programs for school leaders, the activation of organizational learning, and the adoption of proactive crisis management strategies, thereby improving institutional performance within the educational environment. It also suggests conducting in-depth future research to examine the leadership and organizational dimensions associated with institutional resilience across diverse educational contexts.
Keywords: Institutional Resilience; Crisis Management; Public Schools; Sultanate of Oman; Educational Leadership